OFFICE OF RELIGIOUS AFFAIRS BANAWA'S EFFORTS IN MINIMIZING STUNTING CASES IN DONGGALA REGENCY - Susilawati, Susi; Nokoe, Nurhayati Sutan; Pusadan, Sulwan; Nurman, Ilham (Suloh: Jurnal Fakultas Hukum Universitas Malikussaleh, 2024)
This article is based on research entitled "The Role of KUA Banawa in Maximizing Efforts to Accelerate Stunting Reduction in Donggala Regency" motivated by the impact of stunting cases which are very concerning and the rate is getting higher. The impact of stunting is a decrease in intelligence and productivity, susceptibility to disease, thereby hindering economic growth and increasing poverty and inequality which has a long-term effect on themselves, their families, and the Government. Therefore, all efforts and policies to prevent and reduce the stunting rate until now must continue to be tried to overcome it to the maximum.  The role of KUA as a Government at the sub-district level that has religious and family programs is no exception. Indonesia society is a religious society. If the approach through religion and family is expected to help accelerate efforts to reduce stunting in Indonesia, then the role of KUA is highly anticipated. The method used is an empirical legal research method with primary data sources from the Head of KUA Banawa, Banawa District, Donggala Regency.  The conclusion is that the role of KUA Banawa in maximizing efforts to accelerate stunting reduction in Donggala Regency is very important, by requiring health screening and elsimil examination (electronic system ready for marriage, ready to get pregnant) for catin. Collaborate with the District Office, BKKBN, and Puskesmas in participating in implementing regulations on stunting and making it a success.